Viability of Listeria monocytogenes and Salmonella spp. on Slices of a German-Style Bologna Containing Blends of Organic Acid Salts During Storage at 4 or 12°C - John B. Luchansky; Stephen G. Campano; Marcus Rieker; Caroline Mahoney; Bryan T. Vinyard; Laura E. Shane; Bradley A. Shoyer; Manuela Osoria; Anna C.S. Porto-Fett (Journal of Food Protection, 2023)
Viability of cells of Listeria monocytogenes or Salmonella spp. was quantified on slices of a German-style bologna manufactured by a local butcher to contain no added antimicrobials or to include 0.9% or 1.3% of a blend of potassium acetate and sodium diacetate (K-Ace) or 2.5% of a blend of potassium lactate and sodium diacetate (K-Lac) as ingredients. After slicing (ca. 7.1 cm L by 6.7 cm W, ca. 0.5 cm thick, ca. 22.4 g each), a single slice of bologna was placed into a nylon–polyethylene bag and surface inoculated with 250 µL per side of a five-strain mixture of either cells of L. monocytogenes or Salmonella spp. to achieve an initial level of ca. 3.5–4.0 log CFU/slice. The packages were vacuum-sealed and then stored at 4 or 12°C for 90 and 30 days, respectively. Without antimicrobials added to the formulation, L. monocytogenes numbers increased by ca. 5.4 and 6.0 log CFU/slice at both 4 and 12°C during the entire 90- and 30-day storage period, respectively. Likewise, levels of Salmonella also increased by ca. 6.0 log CFU/slice at 12°C in the absence of added antimicrobials; however, levels of this pathogen decreased by ca. 1.7 log CFU/slice after 90 days at 4°C. With the inclusion of 0.9% or 1.3% K-Ace or 2.5% K-Lac in the bologna formulation, levels of L. monocytogenes decreased by ca. ≤0.7 log CFU/slice after 90 days at 4°C, whereas levels of Salmonella decreased by ca. 1.6–2.3 log CFU/slice. After 30 days at 12°C, levels of L. monocytogenes increased by ca. ≤3.4 log CFU/slice on product containing 0.9% K-Ace or 2.5% K-Lac but remained relatively unchanged on slices formulated with 1.3% K-Ace. For Salmonella, in the presence of 0.9% or 1.3% K-Ace or 2.5% K-Lac, pathogen levels decreased by ca. ≤0.7 log CFU/slice at 12°C after 30 days. Our data validate that the inclusion of K-Ace (0.9% or 1.3%) or K-Lac (2.5%) as ingredients is effective for controlling L. monocytogenes and Salmonella on slices of bologna during refrigerated storage.